PENGARUH PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE ANDROID DENGAN WORD OF MOUTH POSITIF SEBAGAI VARIABEL MODERASI - Stefanus Heri Prasetyo Y. Djoko Suseno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The object of this study is to determine the significance effect of perceived value on android smartphone buying decisions; Positive word of mouth influences on android smartphone buying decisions; Positive word of mouth influences on the moderation of perceived value to the android smartphone buying decisions. The population of this study was the Economics Faculty students, University Slamet Riyadi Surakarta using android smartphone, by employing 100 respondents using accidental sampling technique. The technique of collecting data used questionnaires instrument through the stages of testing of validity and reliability first. Test requirements regression used classical assumption. Data were analyzed using double linear regression analysis and absolute difference. The results showed that perceived value is not significant influence on android smartphone buying decisions made by students of the Economics Faculty, University of Slamet Riyadi Surakarta; Positive word of mouth significantly influences android smartphone buying decisions made by made by students of the Economics Faculty, University of Slamet Riyadi Surakarta. Positive word of mouth is not moderate the perceived value of the android smartphone buying decisions made by students of the Economics Faculty, University of Slamet Riyadi Surakarta. Keywords: perceived value, positive word of mouth, buying decisions.